Fabrication and characterization of zinc oxide thin films for optoelectronic applications / Siti Hajar Basri - Siti Hajar , Basri (2017)
Zinc oxide (ZnO) has attracted many attentions recently due its versatility in various semiconductor fields. ZnO has a wurtzite structure with a wide band gap energy of 3.3 eV and very large excitation binding energy which is 60 meV at room temperature. Thus, they are commercially valuable in optoelectronic devices. Some main interests of this material are nontoxic, inexpensive, highly transparent in visible range and conductive in electrical devices. Thus, they are very potential for application in various optoelectronic devices. However, pure zinc oxide thin film naturally has a high resistivity characteristics because of low carrier concentration. In order to improve the conductivity, ZnO thin films were doped with impurities to increase the carrier concentration and/or carrier mobility. In this work, ZnO thin films with Ni-doping were successfully produced by sol-gel spin coating method. Zinc acetate dihydrate was used as the Zn precursor, and nickel (II) acetate tetrahydrate was used as a source of Ni-dopant. The solutions were prepared by dissolving zinc acetate and nickel (II) acetate in ethanol, and diethanolamine (DEA) was used as its chelating agent. Thin films were fabricated by spin-coating method on top of glass substrates. ZnO films underwent pre-heating and post-heating treatment at 300 °C for 10 minutes and 500 °C for 1 h respectively. The influence of nickel in zinc oxide thin film on structural, surface morphology, optical, luminescence, electrical and electronic structure properties were investigated. It is observed that XRD pattern of all thin films are indifferent, with no peak signifying metallic Zn, Ni or NiO. This indicates impurity ions (Ni+) were substituted with Zn atoms which cause no variations in the structural characteristic. FESEM images show the thin films exhibit a smooth surface with grain size of 50 - 70 nm which slightly varies with different Ni concentration. All of the films give high transparency over 80 % in visible range. From the transmittance data, optical band gap of deposited ZnO was calculated to be ~3.30 eV. Photoluminescence result suggested the existing of defect state in Ni-doped ZnO. The resistivity decreases with addition of Ni-doping until it reaches an optimum level at 1.7 x 10-1  cm. The conductivity of Ni-doped ZnO has improved from 0.28 to 5.87 Sm-1; this is 20 times higher than pure ZnO. Further analysis on electrical properties with different temperature has been performed, where the activation energy obtained increases with Ni-doping.